Caracterización clínica y marcadores tumorales para el diagnóstico de cáncer de pulmón. - Tovar Calderón, Karla Gabriela (2024)
Lung cancer is a malignant neoplasm that primarily affects the respiratory system, specifically the lungs. It has a high incidence and mortality rate worldwide, predominantly impacting males. However, there is an increasing number of cases in females. This research was conducted through a literature review to gather scientific information on the clinical characterization and tumor markers for lung cancer diagnosis. It is a descriptive, documentary, non-experimental, retrospective study where 74 scientific articles were reviewed, and 40 articles were selected based on inclusion and exclusion criteria. The information was gathered through an exhaustive search in various databases such as Science Direct, PubMed, Medigraphic, Scielo, Redalyc, eLibro, Portal Regional da BVS, Journal of Cell Biology (JCB), Journal of Contemporary Medicine, and books. The research was concluded through the analysis and discussion of the different studies consulted, achieving the proposed objectives. The average age for lung cancer diagnosis was 60±10 years in males and 58±12 years in females. Males have a higher incidence of this neoplasm, with smoking being the most common risk factor and cough being the most frequent symptom. Regarding the most common histological variant, adenocarcinoma was observed in most patients. The tumor markers used to diagnose and monitor this type of cancer included SCC, CEA, CYFRA 21-1, CA.125, NSE, and ProGRP, which are sensitive and specific for each histological subtype of lungcancer.